2021
DOI: 10.3390/nu13072357
|View full text |Cite
|
Sign up to set email alerts
|

Living with Food Hypersensitivity as an Adolescent Impairs Health Related Quality of Life Irrespective of Disease Severity: Results from a Population-Based Birth Cohort

Abstract: Food hypersensitivity (FHS) refers to food-related symptoms, with or without concurrent Immunoglobulin E (IgE) antibodies related to food(s). It remains unclear how different FHS phenotypes affect health-related quality of life (HRQoL). We examined self-reported HRQoL (with the generic instrument EQ-5D (dimensions and a Visual Analogue Scale (VAS), range 0–100) in association with phenotypes of FHS, and food-specific symptoms among adolescents (n = 2990) from a population-based birth cohort. Overall, 22% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
(66 reference statements)
1
3
1
Order By: Relevance
“…We did not find any association between the number or the severity of reactions (assessed by adrenaline use or the experience of a life-threatening reaction) and the FAQLQ scores, in line with some previous studies on food allergy [30,31,36] or TNPA [9,15]. The experience of a life-threatening reaction correlated with FAIM scores, as expected.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not find any association between the number or the severity of reactions (assessed by adrenaline use or the experience of a life-threatening reaction) and the FAQLQ scores, in line with some previous studies on food allergy [30,31,36] or TNPA [9,15]. The experience of a life-threatening reaction correlated with FAIM scores, as expected.…”
Section: Discussionsupporting
confidence: 91%
“…This was in line with previous studies [30], showing that the burden of food allergy more greatly affects the female population. This was not the case in children and adolescents, even though other studies have reported sex and gender differences in QoL of younger patients with food allergy [15,[30][31][32], possibly because of the male dominance in our pediatric and adolescent population. The impact of sex in allergic diseases has been reported before and has been attributed to the influence of sex steroids on immune responses [33,34].…”
Section: Discussioncontrasting
confidence: 58%
“…1 They may impair school performance, reduce quality of life, and cause severe reactions. 2,3 Parents have frequently concern over the safety of their child at school. Only few studies examine the management of children with allergies at school.…”
Section: Management Of Children With Allergies In Preschool and Schoo...mentioning
confidence: 99%
“…Though evidence suggests a close relationship between psychosocial stress and GI conditions, unexplained food reactions in general, and as potentially related to stress, remain understudied. Unexplained food reactions, or non-allergic food intolerances, which have been defined as non-immunological GI symptoms resulting from the pharmacological response to food components [ 10 , 11 ], are particularly common (15–25%) and underdiagnosed in children [ 12 , 13 , 14 ]. The diagnosis and treatment of unexplained food reactions is potentially challenged because such reactions may be in part related to experiences of stress; however, this remains understudied.…”
Section: Introductionmentioning
confidence: 99%